Sistem Pendukung Keputusan Penentuan Penerima BLT Menggunakan Metode SAW - Pandu Pratama Putra; Dafwen Toresa; Yogi Ersan Fadrial; Puspita Sari; Rometdo Muzawi; Sularno Sularno; Nori Sahrun (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Sidomulyo Village is a village located in the Lyric sub-district, Indragiri Hulu district, Riau Province. According to data obtained by researchers, there were 35 Regency Covid-19 BLT recipients and 51 Provincial Covid-19 BLT recipients. Then there were 95 recipients of BLT DD (Village Fund). In Sidomulyo Village, the recipients of direct cash assistance were only through data collection. This Decision Support System for Determination of Assistance uses the Simple Additive Weighting (SAW) method. The purpose of designing and making a Decision Support System for Determining Direct Cash Assistance is to assist Sidomulyo Village in receiving assistance. In the system that supports direct cash assistance, there are several criteria and alternatives used to determine direct cash assistance. The criteria used are: Occupation, Age, Number of Dependents, Income and Expenditures. While the alternative is all the people listed in the data recipients of direct cash assistance in the village of Sidomulyo. The results of this study are in the form of Determination of Direct Cash Assistance which helps Sidomulyo Village in determining.